Dampak Penerapan Sistem Zonasi dalam Penerimaan Peserta Didik Baru - Mohammad Thoha; H.A. Ghazali (State Islamic Institute of Madura, 2020)
This research aims at analysing the implementation of zoning system and its effect on the Islamic education institution. It also analyses the opportunity and resistance of the implementation of Permendikbud No. 14 2018. The approach of this research is qualitative. The data sources are headmasters, parents or public community dealing with school and all documents related to the content of Permendikbud No. 14 2018. The data collection is done by doing observation, interview and taking the documentation related to the topic. The result shows: first, the response from the institutions under the education and culture department to this regulation are: 1) the state education institution located in the urban area both in the level of elementary and higher school have implemented the regulation; 2) state education institution located in the suburban area have not implemented the regulation; 3) the private education institution and institution under the pesantren’s authority have not implemented the regulation secondly, education institution under the Religious Department got the most positive effect from the regulation of Permendikbud No.14 2018 because the institution under the Religious Department 1) became the first choice because they do not implement the zoning system; 2) are challenged to increase their academic quality to fir the society’s need; 3) got significant additional students; third point is Islamic education institution have a bigger opportunity to get high quality newcomers because the enrolment is not restricted in zone, with change to increase the resources quality and upgrade the school’s image on the society, and also change the student’s enrolment system becomes more innovative.